Rich dynamics of a vegetation–water system with the hydrotropism effect - Li, Li; Wang, Fang-Guang; Hou, Li-Feng (Frontiers in Physics, 2023)
In recent years, with the abnormal global climate change, the problem of desertification has become more and more serious. Vegetation pattern is accompanied by desertification and thus the study of vegetation pattern is helpful to better understand the causes of desertification. In this work, we reveal the influences of hydrotropism on vegetation pattern based on a vegetation-water system in the form of reaction-diffusion equation. Parameter ranges for steady-state mode obtained by analyzing the system and show the dynamic behavior near the bifurcation point. Furthermore, we found that that vegetation hydrotropism not only induces spatial pattern generation, but also promotes the growth of vegetation itself in this area. Therefore, through the study of vegetation patterns, we can take corresponding preventive measures to effectively prevent land desertification and improve the stability of the ecosystem in the region.